Physical activity and sedentary behavior in relation to lung cancer incidence and mortality in older women: The Women's Health Initiative. Issue 10 (15th November 2016) - Wang, Ange; Qin, FeiFei; Hedlin, Haley; Desai, Manisha; Chlebowski, Rowan; Gomez, Scarlett; Eaton, Charles B.; Johnson, Karen C.; Qi, Lihong; Wactawski‐Wende, Jean; Womack, Catherine; Wakelee, Heather A.; et al.
Abstract : Physical activity has been associated with lower lung cancer incidence and mortality in several populations. We investigated these relationships in the Women's Health Initiative Observational Study (WHI‐OS) and Clinical Trial (WHI‐CT) prospective cohort of postmenopausal women. The WHI study enrolled 161, 808 women aged 50–79 years between 1993 and 1998 at 40 U.S. clinical centers; 129, 401 were eligible for these analyses. Cox proportional hazards models were used to assess the association of baseline physical activity levels [metabolic equivalent (MET)‐min/week: none <100 (reference), low 100 to <500, medium 500 to <1, 200, high 1, 200+] and sedentary behavior with total lung cancer incidence and mortality. Over 11.8 mean follow‐up years, 2, 148 incident lung cancer cases and 1, 365 lung cancer deaths were identified. Compared with no activity, higher physical activity levels at study entry were associated with lower lung cancer incidence [ p  = 0.009; hazard ratios (95% confidence intervals) for each physical activity category: low, HR: 0.86 (0.76–0.96); medium, HR: 0.82 (0.73–0.93); and high, HR: 0.90 (0.79–1.03)], and mortality [ p  < 0.0001; low, HR: 0.80 (0.69–0.92); medium, HR: 0.68 (0.59–0.80); and high, HR: 0.78 (0.66–0.93)]. Body mass index (BMI) modified the association with lung cancer incidence ( p  = 0.01), with a stronger association in women with BMI < 30 kg/m 2 . Significant associations with sedentary behavior were not observed. In analyses by lung cancer subtype, higher total physical activity levels were associated with lower lung cancer mortality for both overall NSCLC and adenocarcinoma. In conclusion, physical activity may be protective for lung cancer incidence and mortality in postmenopausal women, particularly in non‐obese women. Abstract : What's New? Physical activity is linked to a reduced risk of lung cancer, though studies have focused primarily on men. Here, lung cancer incidence and mortality were investigated in relation to physical activity in a prospective cohort of postmenopausal women ages 50–79. Lung cancer incidence and mortality were found to be significantly reduced among women whose levels of physical activity were relatively high at the time of study entry. Women who were not obese appeared to experience the greatest protective benefits of physical activity. No associations were found, however, for high physical activity at younger ages or for sedentary behavior.